2022
DOI: 10.3389/fchem.2022.1023602
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots for photothermal applications

Abstract: Carbon dots are zero-dimensional nanomaterials that have garnered significant research interest due to their distinct optical properties, biocompatibility, low fabrication cost, and eco-friendliness. Recently, their light-to-heat conversion ability has led to several novel photothermal applications. In this minireview, we categorize and describe the photothermal application of carbon dots along with methods incorporated to enhance their photothermal efficiency. We also discuss the possible mechanisms by which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Nanosheet is uniformly distributed on the surface of cancer cells. This caused a rapid temperature rise needed for tumor cell death 50 . Lu et al combined the rNGO sheets with MnO 2 nanoparticles.…”
Section: Bio-nanomaterials Used For Pttmentioning
confidence: 99%
“…Nanosheet is uniformly distributed on the surface of cancer cells. This caused a rapid temperature rise needed for tumor cell death 50 . Lu et al combined the rNGO sheets with MnO 2 nanoparticles.…”
Section: Bio-nanomaterials Used For Pttmentioning
confidence: 99%
“…Photo-responsive CDs for tumor therapy mainly include PTT, PDT, and PCT. Considering that recent reviews [49][50][51] have reported advancements in the use of CDs for PTT, in this review, we mainly summarize the latest research progress in PDT and PCT (Table 1).…”
Section: Photo-responsive Cds For Tumor Therapymentioning
confidence: 99%
“…conducted a study on the photothermal conversion efficiency of different CDs and found that factors such as synthesis method, choice of precursors, and functionalization process could significantly affect the band gap energy, thereby influencing the photothermal conversion efficiency. [ 58 ] In the case of CB nanofluids, the temperature can be raised from ≈20 to ≈100 °C after 7 min of exposure, and the heating rate is almost independent of the CB concentration. [ 59 ] Similarly, the CNTs have been demonstrated to have an efficient photothermal conversion property, which can be further improved through functionalization.…”
Section: Photothermal Properties Of Carbonaceous Materialsmentioning
confidence: 99%